2016
DOI: 10.1016/j.joca.2016.01.863
|View full text |Cite
|
Sign up to set email alerts
|

The use of a valgus knee brace on muscle cocontraction during walking and stair climbing in individuals with medial knee osteoarthritis

Abstract: Purpose: Self-reported knee instability is highly prevalent in knee osteoarthritis (OA) and affects daily physical function. An association between knee instability and muscle strength has been demonstrated in cross-sectional studies. However, no information is available on change in self-reported knee instability over time and whether change in muscle strength is associated with change in self-reported knee instability. Muscle strength itself is associated with knee joint proprioception and knee pain. Whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Russell [50] reported that the medial muscle (VM-ST and VM-MG) and lateral muscle (VL-BF and VL-LG) cocontraction indices were not significantly different between MKOA patients and normal person, but the quadriceps strength was significantly lower for MKOA patients. Alzahrani [73] and Hubley-Kozey et al [84] represented that the medial and lateral muscle cocontraction was increased for the KOA patients.…”
Section: Knee Musculoskeletal Disorders and Its Biomechanicalmentioning
confidence: 99%
See 1 more Smart Citation
“…Russell [50] reported that the medial muscle (VM-ST and VM-MG) and lateral muscle (VL-BF and VL-LG) cocontraction indices were not significantly different between MKOA patients and normal person, but the quadriceps strength was significantly lower for MKOA patients. Alzahrani [73] and Hubley-Kozey et al [84] represented that the medial and lateral muscle cocontraction was increased for the KOA patients.…”
Section: Knee Musculoskeletal Disorders and Its Biomechanicalmentioning
confidence: 99%
“…Zhu et al [72] found that the KOA patients presented a longer gait time, a smaller stride length and ROM, a greater knee flexion angle at heel strike, and an unobvious fluctuation of knee flexion angle in the stand phase of walking. Alzahrani [73] indicated that the MKOA patients presented slower walking speeds, shorter step lengths, longer stance and double support time, and smaller cadence, stride length, and knee ROM. In the knee kinetics aspect, Russell [50] described that the knee adduction moment pattern was similar, but the magnitude was higher for MKOA patients compared to that for normal subjects in walking, as shown in Figure 7(c).…”
Section: Knee Musculoskeletal Disorders and Its Biomechanicalmentioning
confidence: 99%
“…Osteoarthritis (OA) is the leading cause of musculoskeletal disability in most developed countries [1][2][3][4]. The prevalence increases with age and is higher in women than in men [4].…”
Section: Introductionmentioning
confidence: 99%
“…OA is characterized by a loss of cartilage in the affected joint, with the knee being the most frequently affected of all joints [1][2][3][4]. The main problems of OA-patients are pain and reduced mobility [1], therefore, patients need walking frames and analgesics [5]. The burden of OA on the population, healthcare system, and the overall economy will continue to increase in the future.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation